Carotid Stenting Versus Endarterectomy for Asymptomatic Carotid Artery Stenosis: A Systematic Review and Meta-Analysis. Issue 10 (22nd June 2022) - Wang, Jie; Bai, Xuesong; Wang, Tao; Dmytriw, Adam A.; Patel, Aman B.; Jiao, Liqun
Abstract : Background: To compare safety and efficacy between carotid artery stenting (CAS) and carotid endarterectomy (CEA) in treating asymptomatic carotid artery stenosis based on results from randomized controlled trials. Methods: Randomized controlled trials comparing CAS and CEA in treating asymptomatic carotid artery stenosis were searched from databases of the EMBASE, PubMed, MEDLINE, and Cochrane libraries. Two independent reviewers identified eligible studies, extracted relevant data, and used the Cochrane risk of bias tool to assess quality. Mantel-Haenszel method random-effects models were used to estimate odds ratio (OR) regarding perioperative risks between CAS and CEA. Kaplan-Meier curve data were extracted and analyzed through Exp[(O-E)/Var] fixed-effect models to calculate the Peto odds ratio (OR) regarding long-term outcomes. Results: Sixteen articles from 7 randomized controlled trials were included, reporting relevant outcomes for 7230 asymptomatic carotid artery stenosis patients (CAS: n=3920; CEA: n=3198). Compared with the CEA group, CAS group had no difference in perioperative composite end point events including stroke, death, and myocardial infarction (MI; OR, 1.13 [95% CI, 0.87–1.47]; P =0.37, I 2 =0%). Compared with CEA, CAS had a higher risk of any stroke during the perioperative period (OR, 1.62 [95% CI, 1.16–2.24]; P =0.004, I 2 =0%) and an increased risk of nondisabling stroke (OR, 1.81 [95% CI, 1.23–2.65]; P =0.003, I 2 =0%), but there was no significant difference in disabling stroke and death between groups (OR, 0.91 [95% CI, 0.50–1.65]; P =0.76, I 2 =0%). For long-term outcomes, no difference regarding the composite outcome of any stroke, death, and myocardial infarction existed between CEA and CAS (Peto OR, 1.18 [95% CI, 0.94–1.48]; P =0.14, I 2 =0%). Individual-level patient data would be important to verify the long-term outcome results. Conclusions: When treating asymptomatic carotid artery stenosis, CAS has comparable perioperative and long-term composite outcomes compared with CEA. However, CAS may have a higher risk of any stroke and nondisabling stroke in the perioperative period.